Pemanfaatan Tehnologi Digital dalam Strategi Pemasaran untuk Meningkatkan Penjualan pada UMKM - Ery Suryanti; Puspa Fortuna Zulfa; Hendra Lesmana; Bernadette Cahya Putri Utami (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study analyzes the use of digital technology in marketing strategies to increase sales. The use of digital technology has become a primary strategy in marketing activities in today's digital era, especially for businesses seeking to increase sales. The purpose of this study was to support the marketing strategy of shop X by utilizing social media and the GoFood app to reach more consumers and increase sales. This study used a qualitative descriptive method. The results indicate that shop X has utilized social media in its sales activities, and its strategy has been able to increase sales. Various promotions have yielded numerous benefits. The study shows that the use of digital technology can increase the effectiveness of promotional activities at an affordable cost and in a short time, facilitating communication with customers, thus increasing sales. The research concludes that one marketing strategy to increase sales is utilizing digital technology, as keeping up with technological developments is crucial for businesses to survive and thrive in the digital economy.